1996
DOI: 10.1111/j.1432-1033.1996.0368z.x
|View full text |Cite
|
Sign up to set email alerts
|

Localization and Regulation of the Putative Membrane Fatty‐Acid Transporter (FAT) in the Small Intestine

Abstract: The expression of the putative membrane fatty-acid transporter (FAT) was investigated in the small intestine. The FAT mRNA level was higher in the jejunum than in the duodenum and was lower in the ileum, as observed for cytosolic fatty-acid-binding proteins (FABP) expressed in this tissue. No FAT transcript was found in the stomach or colon. FAT mRNA was constitutively expressed i n the epithelial cells located in the upper two thirds of villi, while it was undectectable in the crypt cells and submucosal cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
135
2
3

Year Published

1997
1997
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(152 citation statements)
references
References 30 publications
12
135
2
3
Order By: Relevance
“…The radioactive [9, H(N)] triolein (labels were on the 3 FA molecules, not on the glycerol moiety) and [4][5][6][7][8][9][10][11][12][13][14] C] cholesterol were purchased from New England Nuclear (Boston, MA). Silica gel 60 plates were purchased from Fisher Scientific (Pittsburgh, PA) and were activated before use.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The radioactive [9, H(N)] triolein (labels were on the 3 FA molecules, not on the glycerol moiety) and [4][5][6][7][8][9][10][11][12][13][14] C] cholesterol were purchased from New England Nuclear (Boston, MA). Silica gel 60 plates were purchased from Fisher Scientific (Pittsburgh, PA) and were activated before use.…”
Section: Methodsmentioning
confidence: 99%
“…In support of such a role are the high levels of CD36 and its expression pattern along the brush border membrane of the proximal intestine, which is typical of proteins implicated in lipid uptake. 6,7 A recent study by Drover et al 17 showed that CD36 knockout (KO) mice did not exhibit reduced intestinal FA uptake, but had impairments in lymph triacylglcyerol (TG) secretion and in clearance of blood chylomicrons. Whether or not CD36 plays a significant role in intestinal cholesterol uptake and transport in TG-rich lipoproteins in vivo remains unknown.…”
mentioning
confidence: 99%
“…In the GIT, butyrate is naturally present in high concentration in the lumen of the large intestine. It is preferentially taken up by the colonic epithelium where it is actively metabolised to produce energy (3,4) . Much attention has been devoted to the anticancerous properties of butyrate in human nutrition despite numerous papers suggesting its role as a growth factor.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, wc suggested the participation of receptor protein m the fat-sensory mechanism of intestinal epithelial cells [34.35]. In addition, selective expression of FAT in the brush border of jgjunal epithelial cells suggests lhat FAT participates in sensation or absorption of dietary fat [15]. Thus, we conclude that some dietary lat detecting system similar to that in the intestinal epithelium exists in taste cells, and that FAT participates in the sensory mechanism.…”
Section: Resultsmentioning
confidence: 73%
“…Poirier et at. [15] showed that FAT in the jejunal mucosa is expressed in the brush border of epithelial cells, and FAT mRNA in the small intestine is increased by a LCFA-rich diet, suggesting the participation of FAT in the sensation or absorption of dietary fat. We considered that if FAT or related proteins are involved in the sensation of dietary fat in the oral cavity, they must be expressed in taste organ.…”
Section: Introductionmentioning
confidence: 99%